Pemanfaatan Teknologi Digital untuk Pengembangan Desa Toweren - Richasanty Septima S; Ira Zulfa; Syahril Faizin (Institut Teknologi dan Bisnis Semarang, 2024)
Science is developing over time. The development of this science supports the creation of new technologies that mark the progress of the times. One of them is digital technology. Technology in the current era is experiencing rapid development. Technological advances that have gone global have influenced all aspects of life, both in the fields of economy, health, art, public services and education. Digital Technology is an information technology that prioritizes activities carried out by computer or digital rather than using human labor. With the development of digital technology, many fields have benefited from its development. With the development of digital technology, many fields have benefited from its development. With this technology, the village community must also be able to feel the ease of accessing technology because nowadays the village is encouraged to progress and be independent, with the hope of developing the various potentials it has for the progress of its village development, but of course in some villages it is possible not to take advantage of this digital technology because of that community service conducts training. The methods used are training, discussion and practice. The results of the training were a significant increase from 31% to 94% of participants who already understood and knew about the use of digital technology. From the increase in the understanding of village and community officials, it means showing the improvement of the digital literacy skills of the trainees and showing that the goals of this training are quite achievable and successful.